Estrutura de comunidades de formigas no cerrado: diversidade, com-posição e atividade predatória em monoculturas e ecossistemas naturais - Nascimento, Renata Pacheco do (2011)
This study assessed the effect of the structural diversity of the Cerrado vegetation on ant diversity; the effect of conversion of natural areas into crop fields on ant diversity and in their predatory function; and the importance of nature reserves close to crop fields on the ant diversity and predation. I also tested a methodology for collecting hypogaeic ants in the Cerrado. Samples were collected in different areas of Cerrado and at adjacent crop fields. To evaluate the effect of structural diversity of the Cerrado vegetation, ants were collected with pitfall traps and Winkler sacs. To collect hypogaeic ants, initially, I compared trap efficiency at different depths, time of field exposure and the addition of ant attractive and in relation to pitfall traps placed on soil surface. To analyze the effect of the transformation of natural areas into crops fields, epigaeic ants were collected with pitfall traps and hypogaeic ants with subterranean traps, in transects at various distances from reserves. Ant predation in the underground was estimated using Tenebrio molitor larvae buried in traps. On the surface soil and vegetation, ant predation was estimated using artificial caterpillar made with modeling clay. Ant species richness was higher in the cerradão compared to the other types of vegetation, while the vereda had the lowest number of species. Ant species richness was positively correlated with shrub and tree cover, litter cover and biomass, and negatively correlated with grass cover. The species composition also varied according to the structural heterogeneity of the habitats. The most efficient methodology to collect hypogaeic ants consisted of traps exposed for seven days, at 20 cm deep and using palm oil as an additional attractive. The traps placed in the soil surface collect more ants species than subterranean traps and most of the species collected in the underground were also sampled in the surface. However, the subterranean traps collected some species rarely found with other methodologies. The conversion of the natural Cerrado vegetation into crop fields affected ant species richness and composition, with the species found in crop fields being a subset of the species present at the reserves. The predation rate on the soil surface did not differ between the reserves and crop fields, despite the fact that ant species richness was much higher in reserves. In the underground ant predation was higher in the reserves; despite the fact that ant species richness in underground did not differ between the two habitats. It is suggested that differences in predation rates are mediated by differences in total ant abundance rather than by species richness. The distance of the reserves did not affect the structure of ant communities and predation rate in crop fields. Overall, the results of this study suggest that the conservation of ant species diversity depends on the conservation of the habitat mosaic that typically characterize the Cerrado and that farming practices negatively affect the ant species richness and the predatory function performed by these species.